Dosis de compost protowallpa en el desarrollo vegetativo y rendimiento de Panicum máximum cv. tanzania en Loreto, Perú - Caritimari Murayari, Miguel Angel (2025)
The production of pastures in the humid tropics always presents a challenge because the soils are acidic and of low fertility and different forms of fertilization are tested and one of the works presented by the National University of the Amazon in the Faculty of Agronomy is PROTOWALLPA COMPOST DOSE IN THE VEGETATIVE DEVELOPMENT AND YIELD OF Panicum maximum cv. TANZANIA IN LORETO, PERU. It was carried out with a completely randomized block design with four treatments and four repetitions, with an experimental unit of 5 m x 5 m, with the following treatments T0 (0 tons protowallpa compost / ha (Control)), T1 (10 tons protowallpa compost / ha), T2 (20 tons protowallpa compost / ha) and T3 (30 tons protowallpa compost / ha), with the following research results where it can be concluded that the grass Brachiaria brizntha cv. Marandu reacts with a greater increase in its values in the dependent variables as the dose of Protowallpa compost increases under our agroclimatic conditions in the tropical zone. Regarding plant height, treatment T3 (15 tons of compost/ha) obtained 1.52 meters. In green matter of 2.95 kg/m2, dry matter of 0.59 kg/m2, percentage of coverage of 92.52%, weight of leaves of 2.3 kg/m2 and weight of stems of 0.62 kg/m2. In yield per hectare per cut the weight was 29,500 kilos